Primary Care Providers Barriers, Comfort and Awareness in Follow-up Care of Acute Kidney Injury Patients: A Comprehensive Survey on Current Practices - Jean-Maxime Côté; William Beaubien-Souligny; Lauriane Hamel; Josée Bouchard (Canadian Journal of Kidney Health and Disease)
Background: Patients who experienced acute kidney injury (AKI) may benefit from dedicated care following hospital discharge. Most of these patients will be followed by primary care providers. There is a lack of data on current practices and comfort for these care providers when offering post-AKI care. Objective: We surveyed nurse practitioners and family physicians to assess their awareness, perceptions, practice patterns and comfort regarding post-AKI care. Design/Setting: We distributed a web-based self-administered survey among clinicians from the Province of Quebec. We asked about their awareness and perceptions on how AKI should be disclosed and followed, the barriers encountered regarding the process of care following hospital discharge, and their level of comfort and expertise in offering dedicated post-AKI care. The survey integrated direct and scenario-based questions and was conducted from December 2022 to April 2023. Participants: We distributed the survey to practicing family physicians and nurse practitioners through the mailing list of the Fédération des Médecins Omnipraticiens du Québec , and the Association des infirmières praticiennes spécialisées du Québec , respectively. No incentives were provided. Methods: We conducted descriptive analyses and used chi-squared analysis to compare responses between family physicians and nurse practitioners and between hospital-based and cabinet-based practice. Results: The survey was opened by 779 potential participants. Of these, the response rate was 9% (70/779). Most participants were family physicians (79%) and dedicated 70% (±32) of their time in community outpatient clinics. Participants reported that 59% (±20) of all patients seen daily had at least 1 risk factor for AKI, whereas they estimated that 21% (±12) of recently discharged patients suffered from an AKI episode. The lack of awareness by the patient and lack of details on the discharge summary were the barriers most frequently reported impacting the overall process of care at follow-up. Most nurse practitioners (60%) and 33% of family physicians reported at least some levels of discomfort and lack of expertise when offering post-AKI. Limitations: The generalizability of our study is limited by its response rate. However, this is comparable with typical response rates seen in electronic surveys. The distribution was limited to a single province of Canada. Conclusions: We reported significant barriers regarding the hospital-to-community transition of care in patients who experienced AKI and the suboptimal comfort and expertise of primary care providers when offering dedicated post-AKI care. This reflects the need to improve communication, collaboration, and AKI training with primary care providers.